Papel do exercício físico paterno sobre o metabolismo da prole F1 submetida a dieta hiperlipídica - Batista, Rogerio de Oliveira [UNIFESP] (2018)
The role of the father's lifestyle was related in the literature to changes in the offspring phenotype of both genders. Physical training performed during pregnancy can reduce the negative effects of hepatic steatosis mediated by high caloric intake of the offspring through activation of the 5 'activated protein kinase (AMPK) as well as its pathway and targets for its signaling, including the receptor peroxisome alpha (PPARα), peroxisome proliferatoractivated receptor (PGC1α) coactivator 1 and fatty acid synthase (FAS), which will mediate the inhibition of the lipogenesis process and regulation of cellular energy. In addition, paternal and maternal obesity act on the birth weight of the offspring and induce increases in adiposity, glucose intolerance and insulin resistance in the progeny, a central feature of "metabolic programming". Considering the contribution of maternal training, but not of paternal training, on the determination of the offspring phenotype, it is of pivotal importance to analyze the role of the preconception physical exercise performed by the father on the metabolic profile of the next generation (male and female ) associated with the supply of high fat diet for the establishment of obesity. C57BL/6 (F0) mice were matched in sedentary and trained groups. After the training period, the mating occurred with sedentary females and the body weight gain of offspring weaned was observed subsequently. The swimming exercise reduced the FAS and ACC gene expression in the testes as well as increased the protein content of the AMPK in the testes, epididymis and head/body and tail portions. The progeny presented low birth weight at P1, which reached normal weight at P60. During the induction of obesity through the supply of hyperlipid diet (HFD), the male offspring of exercised fathers had lower body weight gain compared to the control group, while the female offspring did not reveal any difference compared to the sedentary counterpart. Glucose intolerance and insulin resistance did not present difference in both proles regardless of the low weight observed in the offspring of exercised fathers. There were no changes in Cpeptide and GIP levels, but reductions were observed in leptin and resistin levels in male offspring of exercised fathers. The level of steatosis in the male offspring of trained fathers was reduced, while the female offspring had the same level of steatosis compared to the control group. The gene expression for Prkaa2, Ppar1α and Cpt1α was increased by paternal exercise in the liver of the offspring compared to the control group but was not regulated in the offspring. Protein content of AMPK was increased in the liver of male offspring but there was no difference in female offspring. Paternal physical exercise was able to regulate the methylation pattern of hepatic DNA in male offspring without substantial changes in female offspring. Together the results suggest a protection against the induction of obesity in progeny mediated by paternal lifestyle in a specificgender. The role of paternal influence can improve the metabolic profile of the offspring and potentiate the oxidative and lipolytic enzymatic activities in the progeny liver, and DNA methylation, playing a brief role in improving the negative effects of obesity.